Clinical Utility of Molecular Tests for Guiding Therapeutic Decisions in Bloodstream Staphylococcal Infections: A Meta-Analysis - Chen, Ke; Malik, Aijaz Ahmad; Sheng, Yun-Jian; Ahmed, Sarfraz; Sun, Changfeng; Deng, Cun-Liang; Ojha, Suvash Chandra (Frontiers in Pediatrics, 2021)
Background: Treatment of bloodstream staphylococcal infections (BSI) necessitates the prompt initiation of appropriate antimicrobial agents and the rapid de-escalation of excessive broad-spectrum coverage to reduce the risk of mortality. We, therefore, aimed to evaluate the diagnostic accuracy of nucleic acid amplification tests (NAAT) for the identification of methicillin-resistant S. aureus (MRSA) and methicillin-sensitive S. aureus (MSSA) in clinically suspected patients. Methods: Until November 23, 2020, databases including PubMed, Scopus, Embase, and Web of Science were scanned for eligible studies. A bivariate random-effects model was used for meta-analysis of the 33 included studies obtained from 1606 citations, and pooled summary estimates with 95% confidence intervals (CI) were generated. Results: Twenty-three studies (n = 8547) assessed NAAT accuracy for MSSA detection, while three studies (n = 479) evaluated MRSA detection in adults. The pooled NAAT sensitivity and specificity for MRSA in adults was higher [sensitivity: 0.83 (95% CI 0.59–0.96), specificity: 0.99 (95% CI 0.98–1.0)] as compared to MSSA [sensitivity: 0.76 (95% CI 0.69–0.82), specificity: 0.98 (95% CI 0.98–0.99)]. Similarly, eight studies (n = 4089) investigating MSSA in pediatric population reported higher NAAT accuracy [sensitivity: 0.89 (95% CI 0.76–0.96), specificity: 0.98 (95% CI 0.97–0.98)] compared to adults. Among NAA tests, SeptiFast (real-time PCR, commercial) was frequently applied, and its diagnostic accuracy corresponded well to the overall summary estimates. A meta-regression and subgroup analysis of study design, sample condition, and patient selection method could not explain the heterogeneity (P >0.05) in the diagnostic efficiency. Conclusions: NAAT could be applied as the preferred initial tests for timely diagnosis and BSI management, particularly in the pediatric population.